Concept of investigation of no-failure system "airplane-crew-medium" with the account of the indefiniteness factor - Ударцев, Е. П.; Журавлева, Л. А. (Proceedings of National Aviation University (archive), 1998)
Proposed is a new approach to estimation of no-failure "airplane-crew-medium" based on modern means and methods of simulation with the account of ageing factor of airplanes. Analyzed is the condition if air fleet of Ukraine which was in operation for a long time